Efficient separation of cathode materials and Al foils from spent lithium batteries with glycerol heating: A green and unconventional way. (1st October 2022) - Gu, Kunhong; Chang, Jiahui; Mao, Xiaohui; Zeng, Hongbo; Qin, Wenqing; Han, Junwei
Abstract: The recycle and reuse of spent lithium-ion batteries are of great environmental and economic significance. Here we succeeded in separating cathode materials from Al foils under an innovative method by the combination of glycerol heating and mechanical stirring. The peel-off rate of cathode material from aluminum foil reaches more than 95% after the treatment under the optimized conditions: heating temperature 200 °C, stirring speed 350 r/min, stirring time 15min. The heat transfer mechanism of cathode materials was determined to adapt theoretical analysis method based on heat conduction differential equation, and the relationship between heating temperature and residence time were accurately calculated. The results infer that the positive electrode sheets can quickly gain the same heat and reach targeted temperature through heated glycerol. The forces on the cathode materials stirred in glycerol were counted into the experiment as well. The stirring speed leading to the isolation of cathode materials from aluminum foils was calculated theoretically based on boundary layer theory and Blasius solution, and the theoretical stirring speed of 239 r/min was concluded by fluid mechanics. Graphical abstract: Image 1 Highlights: Glycerin heating was proposed to separate cathode materials from battery plates. More than 95% of cathode materials were isolated from spent battery plates. The heat conduction and fluid mechanics involved in the process are calculated. The experimental data are verified and interpreted through theoretical calculations.